2013
DOI: 10.1245/s10434-013-3108-1
|View full text |Cite
|
Sign up to set email alerts
|

Operative Risks Associated with Contralateral Prophylactic Mastectomy: A Single Institution Experience

Abstract: CPM patients have an increased risk of complications, especially major complications requiring rehospitalization or reoperation. These complications may influence patient and physician decisions to choose CPM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
70
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(84 citation statements)
references
References 46 publications
6
70
0
8
Order By: Relevance
“…[1][2][3][4][5][6][7] Multiple studies have questioned the benefit of CPM because it does not improve survival in average-risk women [8][9][10][11][12][13] and may increase cost 14,15 and complications. 8,16,17 Numerous studies investigating the increasing use of CPM have identified significant factors related to patient, surgeon, and treatment facility. Patients undergoing CPM tend to be younger, 2-6 have a family history of breast cancer, 1,3 and carry a BRCA mutation.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Multiple studies have questioned the benefit of CPM because it does not improve survival in average-risk women [8][9][10][11][12][13] and may increase cost 14,15 and complications. 8,16,17 Numerous studies investigating the increasing use of CPM have identified significant factors related to patient, surgeon, and treatment facility. Patients undergoing CPM tend to be younger, 2-6 have a family history of breast cancer, 1,3 and carry a BRCA mutation.…”
mentioning
confidence: 99%
“…Breast reconstruction adds substantially to the morbidity 28 and complications commonly affect the prophylactic side in bilateral mastectomy. 31,32 Whilst in the main, patients selecting CPM are satisfied, a proportion of patients will experience regret, issues with body image, challenges forming sexual relationships and lack feelings of femininity. 46 Moreover, whilst few studies explicitly examine cost-effectiveness of CPM, limited data suggests that CPM adds to net costs.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the risk of operative complications is higher with CPM, and in several studies, this risk was double that of UM. [86][87][88] In one single-institution study of 600 patients, 40% of CPM patients had complications compared to 28% of UM patients. Patients who had CPM were 1.5 times more likely to have any complication than UM patients when adjusting for multiple factors and 2.7 times more likely to have a major complication.…”
mentioning
confidence: 99%